Predictors of AF recurrence in patients with paroxysmal AF undergoing catheter ablation: new predictors coming?. (3rd October 2022) - Ribeiro Silva, M; Ribeiro Queiros, P; Santos Silva, G; Teixeira, R; Fernandes, S; Almeida, J; Fonseca, P; Oliveira, M; Goncalves, H; Rodrigues, A; Primo, J; Fontes-Carvalho, R
Abstract: Introduction: Recurrence of atrial fibrillation (AF) after catheter ablation (CA) is estimated to be between 20% and 45% and the prediction of recurrence AF in patients (pts) with paroxysmal AF undergoing CA remains challenging. Purpose: To determine the clinical and procedural predictors of recurrence AF after CA in pts with paroxysmal AF. Methods: Single-centre retrospective study that included all pts with paroxysmal AF who underwent AF CA between 2017 and 2019. Ablation procedures included radiofrequency and second-generation cryoballoon CA. All pts underwent cardiac computed tomography prior the procedure. AF recurrence was defined as any recurrence of AF, atrial flutter or atrial tachycardia >30 seconds (recorded in 12-lead electrocardiogram or Holter) after 90 days of CA. The independent association between clinical and procedural variables and AF recurrence was evaluated with Cox regression analysis. Results: We included 351 pts, 63, 5% male and with a mean age of 57, 1±11, 4 years. CHADSVASCscore ≥2 points were present in 43, 7% of the pts, median duration of AF prior the intervention was 3 years (IQR 1–6) and most pts were treated with some antiarrhythmic drug at the time of CA (56, 9%). Overall, median follow-up was 27 months (IQR 19–39). AF recurrence was present in 96 pts (27, 4%), on average, 15, 2±10, 4 months after CA. Univariate logistic regression identified female gender, thyroid disease, left atrium (LA) enlargement (defined as LA indexed volume >34 mL/m 2 or LA diameter >38mm for female or >40mm for male), coronary calcium score >100, epicardial adipose tissue volume, number of previous electric cardioversions, treatment with antiarrhythmic drugs prior CA and the extent of CA (only pulmonary vein isolation (PVI) or PVI and ablation of other lesions) as predictors of recurrence AF after CA in pts with paroxysmal AF (p<0, 05 for all). Cox regression analysis identified female gender (OR 1, 615, 95% CI 1, 005–2, 597; p=0, 008), LA enlargement (OR 2, 084, 95% CI 1, 207–3, 596; p=0, 008) and coronary calcium score >100 (OR 1, 958, 95% CI 1, 133–3, 385; p=0, 016) as independent predictors of AF recurrence. Conclusions: In our cohort, AF recurrence was significantly higher in pts with LA enlargement, with coronary calcium score >100 and female gender pts. Funding Acknowledgement: Type of funding sources: None.